2017
DOI: 10.1016/j.jcma.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between the MTHFR C677T polymorphism, blood folate and vitamin B12 deficiency, and elevated serum total homocysteine in healthy individuals in Yunnan Province, China

Abstract: The MTHFR C677T polymorphism, folate deficiency, and B12 deficiency were significantly associated with elevated serum tHcy levels. Among these three factors, folate deficiency had the greatest contribution to the serum tHcy concentration, followed by (in order of decreasing effect) MTHFR C677T and vitamin B12 deficiency. Thus, folic acid and vitamin B12 supplementation could help prevent diseases associated with tHcy accumulation, especially in individuals with the MTHFR 677TT genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 56 publications
5
23
0
2
Order By: Relevance
“…In addition, the subjects with TT genotype had significantly higher tHcy levels than those CC genotype (5.44 ± 1.32 μmol/L vs. 4.67 ± 1.07 μmol/L, respectively; P=0.010). The results were consistent with the previous studies [24,43,44]. Because the prevalence (19%) of 677TT genotype is high in China, the risk of exposure to plasma folate deficiency, resultant hyperhomocysteinemia, and adverse pregnancy outcome may elevate [45][46][47].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the subjects with TT genotype had significantly higher tHcy levels than those CC genotype (5.44 ± 1.32 μmol/L vs. 4.67 ± 1.07 μmol/L, respectively; P=0.010). The results were consistent with the previous studies [24,43,44]. Because the prevalence (19%) of 677TT genotype is high in China, the risk of exposure to plasma folate deficiency, resultant hyperhomocysteinemia, and adverse pregnancy outcome may elevate [45][46][47].…”
Section: Discussionsupporting
confidence: 92%
“…The increase in the frequency of pathological alleles of the folic acid cycle genes in women with disorders of the pregnancy course, as compared to the control group, revealed in the present study is supported by numerous literature data, for example [9]. However, the lack of direct correlation between the genotype of the four most clinically significant SNPs and the blood homocysteine level detected is in some contradiction with the literature data, for example [10]. This phenomenon can be pretty explained, on the one hand, by the features of the sample being analyzed and on the other hand, by the difference in the mean square deviation of the homocysteine level fluctuation over time in specific patients.…”
Section: Discussionsupporting
confidence: 70%
“…Elevated homocysteine level can be either due to deficiency of folate or Vitamin B 12 [20]. A recent study carried out in China among 330 study volunteers also reported folate and Vitamin B 12 deficiency as well as MTHFR C677T polymorphism were significantly associated with elevated serum homocysteine levels [21]. Higher prevalence of hyperhomocysteinemia has been reported among vegetarians mainly due to Vitamin B 12 deficiency [22].…”
Section: Research Articlementioning
confidence: 99%